Acute lysine overload provokes marked striatum injury involving oxidative stress signaling pathways in glutaryl-CoA dehydrogenase deficient mice. (October 2019) - Amaral, Alexandre Umpierrez; Seminotti, Bianca; da Silva, Janaína Camacho; de Oliveira, Francine Hehn; Ribeiro, Rafael Teixeira; Leipnitz, Guilhian; Souza, Diogo Onofre; Wajner, Moacir
Abstract: Glutaric acidemia type I (GA I) is a neurometabolic disorder of lysine (Lys) catabolism caused by glutaryl-CoA dehydrogenase (GCDH) deficiency. Patients are susceptible to develop acute striatum degeneration during catabolic stress situations whose underlying mechanisms are not fully established. Thus, in the present work we investigated the effects of a single intrastriatal Lys administration (1.5–4 μmol) to 30-day-old wild type (WT) and GCDH deficient ( Gcdh−/− ) mice on brain morphology, neuronal injury, astrocyte reactivity and myelin structure, as well as signaling pathways of redox homeostasis. We observed a marked vacuolation/edema in striatum and at higher doses also in cerebral cortex of Gcdh−/−, but not of WT mice. Lys also provoked a reduction of NeuN and synaptophysin, as well as an increase of astrocytic GFAP, in the striatum of Gcdh−/− mice, indicating neuronal loss and astrocyte reactivity. Furthermore, we verified an increase of Nrf2 and NF-κB expression in the nuclear fraction, and a decrease of heme oxygenase-1 (HO-1) content in the striatum of Lys-injected Gcdh−/− mice, implying disruption of redox homeostasis. Finally, it was found that Lys provoked alterations of myelin structure reflected by decreased myelin basic protein (MBP) in the cerebral cortex of Gcdh−/− mice. Taken together, the present data demonstrate neuronal loss, gliosis, altered redox homeostasis and demyelination caused by acute Lys overload in brain of Gcdh−/− mice, supporting the hypothesis that increased brain concentrations of glutaric and 3-hydroxyglutaric acids formed from Lys may be responsible for the acute brain degeneration observed in GA I patients during episodes of metabolic decompensation. Highlights: Acute Lys overload provoked vacuolation in striatum and cerebral cortex of Gcdh−/− mice. Acute Lys overload caused neuronal and astrocytic damage in striatum of Gcdh−/− mice. Oxidative stress signaling pathways were involved in the Gcdh−/− mice striatum injury. Acute Lys overload altered myelin structure in cerebral cortex of Gcdh−/− mice.